Learning from autistic teachers : how to be a neurodiversity-inclusive school - Wood, Rebecca; Crane, Laura; Happé, Francesca; Morrison, Alan; Moyse, Ruth (Jessica Kingsley Publishers, 2022)
In this strikingly honest collection, developed from a pioneering new research project, autistic teachers and other autistic school professionals share their stories of the challenges and successes of their careers. Contributors challenge assumptions and stereotypes whilst highlighting the unique strengths autistic staff can bring to schools when their own needs are accommodated. The book explores exclusion and identity, understanding and acceptance, intersectionality and facilitating inclusion. It also celebrates the positives that come with being an autistic teacher, such as relating to neurodivergent pupils and conveying passion and enthusiasm for a subject through intense interests, or demonstrating particular skills in school leadership. It examines how workplace set up can sometimes exclude autistic individuals and lead to skilled teachers and those in other education roles, including visiting professionals, leaving the profession, and sets out the accommodations that can prevent this from happening.
Keywords: Teachers with disabilities.; Autistic people -- Employment.; Inclusive education.; Autistic people.; Mainstreaming, Education.; Enseignants handicapés.; Autistes.; Intégration scolaire.; Autistes -- Travail.; Autistic people; Inclusive education; Teachers with disabilities